Differential Functionalization of 1, 6‐Naphthyridin‐2(1H)‐ones through Sequential One‐Pot Suzuki–Miyaura Cross‐Couplings. Issue 7 (8th January 2014) - Montoir, David; Tonnerre, Alain; Duflos, Muriel; Bazin, Marc‐Antoine
Abstract: A practical synthesis of 7‐chloro‐3‐iodo‐1‐methyl‐1, 6‐naphthyridin‐2(1 H )‐one is described that starts from 2‐chloro‐4‐(methylamino)nicotinaldehyde. The dihalo compound then undergoes sequential, site‐selective Suzuki–Miyaura cross‐coupling reactions to afford highly functionalized 1, 6‐naphthyridones in good yields. Abstract : One‐pot, sequential, site‐selective Suzuki–Miyaura cross‐coupling reactions of 7‐chloro‐3‐iodo‐1‐methyl‐1, 6‐naphthyridin‐2(1 H )‐one afforded highly functionalized 1, 6‐naphthyridones in good yields.